Epidemiological aspects of illness and injury - Vleck, V.; Hoeden, D. (Triathlon Medicine, 2019)
Advances in epidemiological research into maladaptation in triathletes have largely been hampered by inconsistent definitions of injury and illness between studies, poorly described sample populations, and small sample sizes. This chapter presents the results of five consecutive triathlon-specific studies, all of which used consistent data collection methods and definitions, with a total subject number of 2216. The ensuing data are easily divisible into gender-, athlete ability-level- and event distance specialization-specific subgroups. The results of these three retrospective surveys, one prospective medical tent-based observational study and one prospective longitudinal training diary-based survey, in conjunction with our 2014 review of the impact of triathlon training and racing on athletes' general health, allow us to furnish the reader with an updated snapshot of current knowledge as regards the extent of, and potential risk factors for, triathlete injury and illness. Synergistic collaboration between all stakeholders is a prerequisite for further advancement towards the best applied model for reducing the risk of injury and illness in triathletes.